Risk Factor Pattern of Graves’ Ophthalmopathy at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia - Akbar, Royhan; Mudjanarko, Sony Wibisono; Komaratih, Evelyn; Ardiany, Deasy (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2025)
Highlights: Female patients are more likely to suffer from GO. Most GO patients have high thyroid levels (hypothyroidism).   Abstract Introduction: Graves' ophthalmopathy (GO) is an autoimmune condition that extends beyond the thyroid gland. The development of GO may be influenced by various risk factors, some of which may interact with each other. This study aimed to identify the most prevalent risk factors for patients with GO from 2019 to 2022 at Dr. Soetomo General Academic Hospital, Surabaya. Methods: This study employed a descriptive cross-sectional design, examining 150 patients who met the inclusion and exclusion criteria. This study measured the age, gender, and systemic thyroid status of all patients. This study used Microsoft Word and Microsoft Excel for Mac version 16.87 to process data. Results: Between 2019 and 2022, 150 patients were diagnosed with GO at Dr. Soetomo General Academic Hospital, Surabaya. The condition was more prevalent in females than males, and the most common age group affected was between 30 and 50 years old. Additionally, 72% of patients with GO also had hyperthyroidism. Conclusion: Graves' ophthalmopathy was more prevalent in female patients, aged between 30 and 50 years old, with the majority having hyperthyroidism. Future studies should be conducted on the patterns of GO risk factors on a larger scale to more accurately represent the disease in the general population.